2014
DOI: 10.1017/s0033291714001597
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization: a systematic review on its clinical characterization

Abstract: Studies addressing the incremental value of demoralization in psychiatry and psychology are needed. However, demoralization appears to entail specific clinical features and may be a distinct condition from major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 132 publications
9
121
0
1
Order By: Relevance
“…Demoralization is defined as a psychological state characterized by both hopelessness and helplessness, and the inability to cope with stress that is expected to be handled by every individual [26, 27]. It is therefore possible that the symptoms experienced by the patient and assessed with the DASS-21 at admission are more likely to reflect a temporary negative emotional state due to the factors mentioned before, rather than a depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Demoralization is defined as a psychological state characterized by both hopelessness and helplessness, and the inability to cope with stress that is expected to be handled by every individual [26, 27]. It is therefore possible that the symptoms experienced by the patient and assessed with the DASS-21 at admission are more likely to reflect a temporary negative emotional state due to the factors mentioned before, rather than a depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Demoralization and major depression can be differentiated on clinical grounds; they may occur together or independently, and major depression does not necessarily involve demoralization [106]. DCPR studies on demoralization reported very low prevalence in healthy participants (not higher than 2-5%) and a high prevalence in the medically ill (about 30%) [106].…”
Section: Psychosomatic Assessment and Individualized Carementioning
confidence: 99%
“…Demoralization and major depression can be differentiated on clinical grounds; they may occur together or independently, and major depression does not necessarily involve demoralization [106]. DCPR studies on demoralization reported very low prevalence in healthy participants (not higher than 2-5%) and a high prevalence in the medically ill (about 30%) [106]. Table 12 shows the revised DCPR criteria for demoralization and its two different expressions: helplessness (the individual maintains the capacity to react but lacks adequate support) and hopelessness (when the individual feels he/she alone is responsible for the situation and there is nothing he/she or anyone else can do to overcome the problem) [107].…”
Section: Psychosomatic Assessment and Individualized Carementioning
confidence: 99%
“…Demoralization is a psychological state characterized by helplessness, hopelessness, sense of failure and a feeling of inability to cope [4,5]. Frank's [4] original clinical hypothesis argues that demoralized patients more frequently and actively seek psychotherapy and respond readily to help and encouragement, that is to nonspecific psychotherapeutic factors.…”
Section: Figmentioning
confidence: 99%